Recidivism and neighborhood institutions: evidence from the rise of the evangelical church in Chile - Barrios-Fernandez, Andres (2021)
Rehabilitating convicted criminals is challenging; indeed, an important share of them return to prison only a few years after their release. Thus, finding effective ways of encouraging crime desistance, particularly among young individuals, has become an important policy goal to reduce crime and incarceration rates. This paper provides causal evidence that the local institutions of the neighborhood that receives young individuals after prison matter. Specifically, we show that the opening of an Evangelical church reduces twelve-months re-incarceration rates among property crime offenders by more than 10 percentage points. This effect represents a drop of 16% in the probability of returning to prison for this group of individuals. We find smaller and less precise effects for more severe types of crime. We discuss two classes of mechanisms that could explain our results: religiosity and social support. We provide evidence that the social support provided by evangelical churches is an important driver of our findings. This suggests that non-religious local institutions could also play an important role in the rehabilitation of former inmates